An assessment of corruption factors and impact from the perspective of professional bodies in the built environment - Hashim, Khairusy Syakirin Has-Yun; Abdullah, Muhammad Faris; Rabe, Noor Suzilawati; Ab Sani, Jasasikin; Sapian, Abdul Razak; Ibrahim, Izihan; Mohd Abbas, Abazazilah (Malaysian Institute of Planners, 2025)
The built environment sector is highly vulnerable to corruption due to its complex processes, multiple stakeholders, and large financial flows. This study examines the factors and impacts of corruption from the perspective of registered members of professional bodies in the built environment sector in Malaysia. It adopts a quantitative approach where an online survey was distributed among members of the professional bodies, yielding 417 valid responses. Relative Importance Index analyses revealed that the main factors driving corruption are the need “To obtain approval quickly” and “Low ethics and integrity.” Respondents also agreed that “Poor reputation of professional bodies/the sector” and “Non-compliance with standards” as the most significant impacts of corruption. The results also suggest that corruption is less about external pressures and more linked to systemic weaknesses and individual ethical failings. Hence, the study recommends the professional bodies to undertake rigorous awareness campaigns and continuous training for both new and long-serving members, and to adopt Organisation Anti-Corruption Plan as a platform to embed anti-corruption initiatives and integrity values in their organisational culture as well as among members. The study also suggests for a more streamlined and simplified project approval process to reduce corruption risks